Joint bending stiffness and internal force calculation of assembled pipe jacking - Xin Feng; Peng Zhang; Baosong Ma; Hao Zhou (地质科技通报, 2021)
With the increasing of the cross section area of pipe jacking, the transportation problem of pipe is becoming more and more serious.And the assembled pipe jacking technology can effectively solve this problem.Based on the existing assembled structural joints, the connection method of the assembled pipe transverse joint is put forward.Then, the bending stiffness model of transverse joint in bolt assembled pipe is established, and the structural calculation method of assembled pipe is put forward with reference to the beam-spring model of shield segment.The results of internal force show that the internal force distribution of assembled and integral pipe is basically the same; the bending moment of the side wall of the assembled pipe is less than that of the integral pipe, while the bending moment at the top and bottom is greater than that of the integral pipe and there is no sharp change in their internal forces; in terms of internal force distribution and value, the assembled pipe is available.